Impulse balance and framing effects in threshold public good games. (25th January 2019) - Cartwright, Edward; Stepanova, Anna; Xue, Lian
Abstract : In this paper, we revisit the evidence for framing effects in threshold public good games. Our particular focus is on why the probability of providing the public good appears to be higher in positive, give frames compared with negative, take frames. We show that the impulse balance theory can explain this effect. We also report a new experiment designed to test the predictions of the impulse balance theory. The results of the experiment fit well, both in quantitative and qualitative terms, with our predictions.